Patho-morphological changes in kidneys of pigeons in case of spontaneous colibacillosis - Панікар, І. І.; Скрипка, М. В.; Коломак, І. О. (Scientific Progress & Innovations, 2016)
The results of epizootic situation monitoring, held in the town of Poltava concerning wild pigeons’ diseases, have been presented in the article. The spreading of colibacillosis causal agent, E. coli among pigeons has been studied. Based on the held patho-morphological examinations, the peculiarities of changes in kidneys in case of spontaneous colibacillosis, have been revealed. The changes have been characterized by the signs of focal interstitial purulent inflammation, granular degeneration, and the formation of hemosiderin. In case of chronic course of disease, patho-morphological changes have been accompanied by the formation of granulomas and proliferation of connecting tissue.